Motivasi Pengembangan dan Pematangan Karir Kewirausahaan di Pondok Pesantren (Kajian di Pondok Pesantren Al-Rabbani Cikeas) - Nani Almuin; Solihatun Solihatun; Sugeng Haryono (Sosio e-Kons, 2017)
ABSTRACT Entrepreneurship education not only teaches in a public school science course but this time entrepreneurship has become a trend today that has been widely adopted by educational institutions based schools. Santriwan entrepreneurial learning curriculum and female students form a moderate boarding school after graduation is not only a tutor but can build an entrepreneurial career as a pious and fair. This study uses descriptive Qualitative analysis based on the analysis of modern pesantren institutions that have been successful in running the entrepreneurship curriculum. Motivation career development and maturation in the boarding school al Rabbani generally can be done, just need to be given the maturity and debriefing basics of entrepreneurship to be more effective. Motivational counseling and debriefing program development and maturation of entrepreneurial career in boarding school Al Rabbani aiming to make dropout to be creative, innovative and mature to build a career in the field of entrepreneurship. With the knowledge of entrepreneurship into capital and the best way towards a successful entrepreneur.Keywords: Education, motivation, entrepreneurship, career, management, and development ABSTRAKPendidikan kewirausahaan tidak hanya di ajarkan di sekolah umum saja namun saat ini ilmu kewirausahaan sudah menjadi trend masa kini yang sudah banyak diterapkan oleh lembaga pendidikan berbasis pesantren. Kurikulum pembelajaran kewirausahaan membentuk santriwan dan santriwati pondok pesantren yang moderat, setelah lulus tidak hanya menjadi guru mengaji namun bisa membangun karir menjadi seorang wirausaha yang soleh jujur dan adil. Penelitian ini menggunakan metode kualitiatif deskriftif analisis berdasarkan analisis lembaga pesantren modern yang sudah sukses dalam menjalankan kurikulum kewirausahaan. Motivasi pengembangan dan pematangan karir di pondok pesantren al Rabbani umumnya bisa terlaksana, hanya saja perlu diberikan kematangan dan pembekalan dasar-dasar ilmu kewirausahaan agar lebih efektif. Program penyuluhan dan pembekalan Motivasi pengembangan dan pematangan karir kewirausahaan di pondok pesantren Al Robbani bertujuan menjadikan remaja putus sekolah menjadi kreatif, inovatif serta matang membangun karir di bidang wirausaha. Dengan bekal ilmu kewirausahaan menjadi modal dan cara yang terbaik menuju seorang wirausahawan yang sukses.Kata kunci : Pendidikan, Motivasi, Kewirausahaan, karir, pengelolan dan pengembangan